(untitled) (Altre Modernità, 2019)
Through a continuous confrontation of two testimonial texts of the writer and survivor of the Pinochet dictatorship, Nubia Becker, this article intends to analyse the symbols that, in spite of the context of violence and torture, testify to a dense context of resistance, resilience, dignity, and solidarity. The article intends to trace the pathof metamorphosis of the text which, like the evolution in the Chilean socio-political context (between 1973 and 2011), demonstrates the leading role of women against the Pinochet dictatorship. At the same time, through a metaphorical analysis (cfr. Durand), we intend to offer a non-exhaustive table between real issues and symbolic meanings, as in the case offered by the cracks that illuminate the paradigmatic obscurity of the detention and torture camps. Therefore, the symbol is interpreted through a collective methodology (cfr. Halbwachs) to elaborate "imaginary of the daily life of the political prison from the data, vestiges, anecdotes and dreams that the plural memory provides" (Montealegre Memorias 185).